Manajemen Risiko Kesehatan dan Keselamatan Kerja Menggunakan Metode HIRARC Pada Project Pembangunan Gedung Universitas Nahdlatul Ulama Yogyakarta - Mardhatillah, Vina; Nasrulloh, Rifqi Syarif; Suhada; Idries, Fahmy Akbar (Jurnal Manajemen, 2023)
Work accidents can occur due to the actions of someone who does not comply with work safety, carelessness of workers, unsafe procedures. The purpose of this research is to compare the risk management plan implemented by the company with the results of the research that has been done. The research was conducted using a descriptive method that describes the identification and assessment of OSH risks. Retrieval of data regarding identification and risk assessment is analyzed with HIRARC (Hazard Identification Risk Assessment and Risk Control), evaluated and determined efforts to improve and control hazard risks in the workplace so that the workplace is safe. The results of this study are the results of a risk assessment in the early stages of identifying company risks, there are potential occurrences of 18 types of risks. However, through the results of further research in the risk identification process, there are a total of 23 types of risks identified in column formwork and work at height. Risk control efforts include the use of proper PPE as well as regular inspections on scaffolding. Some risks do not occur according to initial predictions, and some unexpected risks arise. Even so, preventive measures are still being implemented to minimize the impact that may occur.